Influence of Aggregates on Stripping Behavior of Bituminous Mixes - Hillol Chakravarty; Sanjeev Sinha; Girijesh Kumar (Salehan Institute of Higher Education, 2021)
Moisture damage leads to premature failure of flexible pavements. The removal of bituminous coating from aggregates lead to the disintegration of bituminous mixes and is known as stripping. Various mechanisms and factors have been identified to play a role in the process, properties of aggregates being one of the major factors. This study is an attempt to analyze the influence of chemical, mineralogical and physical properties of aggregates on the stripping propensity of the loose mix. For this purpose, aggregates are chosen from six different quarry sites with diverse chemical compositions used for construction and maintenance of a large network of roads. Stripping tests are thereafter conducted on the aggregates using different percentage of hydrated lime. The amount of hydrated lime required for the prevention of stripping for concerned aggregate sources is determined. The research leads to the findings that the presence of elements such as silicon and potassium leads to a decrease in bond strength whereas the presence of calcium, sodium, iron, magnesium and aluminium enhanced the bond strength. Statistical tools and techniques are used to verify the results. Comparatively softer aggregates showed lesser resistance to stripping which could be inferred from aggregate impact and Los Angeles abrasion tests. The findings of the study can be helpful in the selection of aggregates with different chemical content for bituminous road construction depending upon the sensitivity to stripping. Doi: 10.28991/cej-2021-03091671 Full Text: PDF